Implementasi Kurikulum Merdeka Belajar Pada Pembelajaran Pendidikan Agama Kristen Kelas XI Di SMK St. Nahanson Sipoholon Tahun 2023 - Dermawati Purba; Limmarten Simatupang; Masniar Sitorus; Goklas Manalu; Andrianus Nababan (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The purpose of this research is to find out how the Independent Learning Curriculum is implemented in Class XI Christian Religious Education at St. Vocational School. Nahanson Sipoholon in 2023. The method used in this research is mixed methods. This research is a research step that combines two previously existing forms of research, namely qualitative research and quantitative research. For interviews, the population of school principals was 1 person and Christian Religious Education teachers were 2 people. The interview used is an in-depth interview or commonly known as an in-depth interview which is usually aimed at obtaining in-depth information and is developed according to the situation and conditions in the field. The interview data in the form of statements contained 15 items. So the results obtained in all interviews were in the very good category with a percentage of 97.7%, then the very poor category with a percentage of 2.23%. The population for the questionnaire was all class XI students who adhere to Protestant Christian beliefs at St. Vocational School. Nahanson Sipoholon learning in 2023/2024 is 131 people and a sample of 58 people was taken using random sampling techniques. Data was collected using a positive closed questionnaire with 26 items. The results of data analysis show that the overall percentage of the implementation of the independent learning curriculum in class XI Christian religious education at St. Vocational School. Nahanson Sipoholon in 2023 is 72.94% and is in the good category, namely in the interpreted value between 61%-80%.